Life-cycle greenhouse gas assessment of Community Supported Agriculture in California's Central Valley. Issue 5 (1st June 2017) - Christensen, Libby O.; Galt, Ryan E.; Kendall, Alissa
Abstract: Many consumers are trying to reduce their food's environmental impact by purchasing more locally sourced food. One choice for local food is Community Supported Agriculture (CSA), in which farmers provide a share of produce on a regular basis to pre-paying farm members. The number of CSAs in the USA has grown from two in the mid-1980s to perhaps as many as 12, 617 according to the latest US census of agriculture (2014). We use a case study approach to investigate the greenhouse gas (GHG) emissions associated with five CSA operations in the Sacramento Valley of California. By understanding the GHG emissions of CSAs and the practices that might be improved, we hope to support innovative strategies to reduce GHG emissions in these agricultural production systems. Input, production and distribution data were collected from each farm and reported in CO2 e emissions for 1 kg CSA produce at the pickup location. Results show large variation in total emissions, ranging from 1.72 to 6.69 kg CO2 e kg −1 of produce with an average of 3.94 kg CO2 e kg −1 produce. The largest source of emissions was electricity, contributing over 70% of total CO2 e emissions on average. Based on our findings, despite the seemingly similarities between these operations in terms of production site, acreage, customers and production practices, there is still a large amount of variability with regard to total GHG. Thus we argue coming up with a standardized production function for diversified production and deriving GHGs or calculating average total emissions overlooks the heterogeneity of the system. Food systems can never be reduced to a simple binary of local is better and conventional is worse, or its inverse local is worse and conventional is better, because of the complexities of the production and distribution systems and their relationship to GHG emissions. Yet, we can say that localized production systems that are low in electricity use (or use renewable energy sources) and use efficiently-produced compost use have lower GHG emissions than those that do not.